Identification of fungi isolated from clinical wastes - Noman, Efaq Ali; Al-Gheethi, Adel; Talip, Balkis; Ab. Rahman, Nik; Nagao, Hideyuki; Radin Mohamed, Radin Maya Saphira; Ab. Kadir, Omar (UTHM Publisher, 2017)
The distrubition of fungi in the hospitals wastes are coming from the clinical wastes specimens used for the disgnistic process. The aim of the present study was to identify the fungal isolates obtained from clinical wastes based on phenotype method. The fungal isolates were obtained by the direct plate method on Potato Dextrose Agar (PDA) medium and incubated at 28◦C for 7 to 14 days, therafter purified by single spore isolation. The cultural characteristics of the fungal isolates were described on different media, while the morphologies were observed using a light microscope. Eight fungal species from five genera were identified and included Curvularia Trichoderma spp. Rhizopus sp. Fusarium spp. Oidiodendron sp. These results indicated that the clinical wastes have a diversity of fungi which might possess health risk to humans if these fungi have not inactivated in the clinical wastes before the final disposal into the environment.